Managing and reporting of shari’ah non-compliant income in Malaysian Islamic banks / Norhanizah Johari - Johari, Norhanizah (2021)
Compliance is one of the core elements of good governance that supports the growth and development of the Islamic finance industry through good governance and comprehensive legal frameworks. Fitting conventional banking and finance features into Islamic banking and finance has exposed Islamic Financial Institutions (IFIs) to Shariah Non-Compliance Risk (SNCR). Therefore, the Shariah Compliance and Governance Framework is essential to guide the banks on the regulatory requirement. For instance, both Section 28(1) and Section 28(3) of the Islamic Financial Services Act (IFSA) 2013 emphasized IFI’s compliance to the Shari’ah principles at all times in all their activities and, to manage and report their Shari’ah Non-Compliance (SNC) incidents. One of the examples of SNC incidents is Shariah Non-Compliant Income (SNCI) that could impact the profit of the bank, which emerged from the Shari’ah Non-Compliance Event (SNCE). This study purports to understand SNC incidents by exploring the end-to-end process of managing and reporting of SNCI for IBs in Malaysia and thus fulfills the following research objectives; (1) to explore the occurrence of SNCI incidents in Islamic Banks in Malaysia ; (2) to explore the current practices in managing and reporting of SNCI by relevant key functions in Islamic Banks in Malaysia.; (3) to investigate the current processes in rectification, purification, and disposal of SNCI by IBs in Malaysia; and finally to propose a guideline of best practice in managing and reporting of SNCI for IBs in Malaysia. The context of this study is based on the stewardship theory in which the people and process are the key components of Shari’ah Governance and the issue of accountability and transparent disclosure of SNCI are the central issue of this study. Henceforth, in-depth interviews with the bank’s key functions and the Shari’ah scholars, documentations review and the content analysis on Financial Reporting for Islamic Banking Institutions, Shari’ah Governance Policy, Operational Risk Integrated Online Network (ORION) policy document, and the annual reports of the ten participating IBs were conducted to fulfill the delineated research objectives. ‘The Six Phases of Reflexive Thematic Analysis’ was applied to explore and develop an understanding of patterned meaning across the datasets, eased by Atlas.ti software. The findings indicated the infused prudence in stewardship theory would promote greater accountability and transparency in managing and reporting of SNCI, thus enhance the credibility, reputation, and corporate image of IBs in the eyes of multiple stakeholders.